2016
DOI: 10.1002/cctc.201601060
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Palladium‐Catalyzed Hydrogen‐Transfer Cyclization of Nitroacetophenones with Benzylamines: Access to C−N Bonds

Abstract: The first Pd/C‐catalyzed oxidative C(sp3)−H bond amination of o‐nitroacetophenones with benzylamines or amino acids proceeding through C−N bond cleavage followed by C−N bond formation by a hydrogen‐transfer strategy was developed. These transformations proceeded smoothly in water to afford the desired quinazolines in moderate to good yields. This protocol has a broad substrate scope and good tolerance of air, offers excellent recyclability of the catalyst, and does not need any additional oxidant, ligand, or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 101 publications
1
4
0
Order By: Relevance
“…The one-pot reactions lead to the high yield formation of the corresponding quinazoline products. Furthermore, control experiments (Figure S11) corroborate what has been reported in the related organic reactions 54,55 and indicate that the formation of quinazoline follows a reaction mechanism similar to that outlined in Scheme S3.…”
supporting
confidence: 82%
“…The one-pot reactions lead to the high yield formation of the corresponding quinazoline products. Furthermore, control experiments (Figure S11) corroborate what has been reported in the related organic reactions 54,55 and indicate that the formation of quinazoline follows a reaction mechanism similar to that outlined in Scheme S3.…”
supporting
confidence: 82%
“…For the synthesis of quinazolines, Tang et al reported a heterogeneous Pd/C‐catalyzed hydrogen‐transfer cyclization of nitroacetophenones with various benzylamines through C−N bond cleavage followed by C−N bond formation in water [Eq. (77)] …”
Section: Applications Of Pd/cmentioning
confidence: 99%
“…The first example of the reaction of o -nitroacetophenones with benzyl amines or amino acids catalyzed by Pd/C in water at 140°C for 24 h produced quinazolines in 37%–89% yields ( Scheme 19D ). ( Tang et al, 2016 ) The reaction proceeded in a C-N bond cleavage formation sequence. Furthermore, when amino acids were used as substrates, the product was synthesized via decarboxylative oxidative amination.…”
Section: Second-row Transition Metal Catalystsmentioning
confidence: 99%
“…Rh-AVC can be readily generated from N-sulfonyl-1,2,3-triazoles via denitrogenation catalyzed by the Rh(II) system and is widely used as a [1C]-, [2C]-, and aza-[3C]component in several transformations (Miura et al, 2012;Lei et al, 2015;Ryu et al, 2015). Interestingly, Tang et al (2016) reported an unprecedented Rh(II)-catalyzed transannulation of 2,1-benzisoxazoles 118 with N-sulfonyl-1,2,3-triazoles 119. The cycloaddition of 2,1-benzisoxazoles 118 with N-sulfonyl-1,2,3triazoles 119 catalyzed by Rh 2 (esp) 2 in 1,2-DCE at 160 °C for 5 min and then with DBU at room temperature for 30 min delivered quinazolines 120 in 35%-83% yields (Scheme 17C).…”
Section: Rhodiummentioning
confidence: 99%